The valley of amazement - Tan, Amy (New York : Ecco, 2013)
Violet Minturn, a half-Chinese/half-American courtesan who deals in seduction and illusion in Shanghai, struggles to find her place in the world, while her mother, Lucia, tries to make sense of the choices she has made and the men who have shaped her.
Keywords: Americans -- China -- Fiction; Historical fiction